HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN RESILIENSI AKADEMIK SISWA DI SMA SWASTA ISTIQLAL DELI TUA - Pipit Sundari; Khairina Ulfa Syaimi; Ika Sandra Dewi; Dina Hidayati Hutasuhut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research aims to explore the correlation between peer social support and academic resilience among 137 Grade XI students at Istiqlal Private High School, Deli Tua, during the 2024/2025 academic year, using a quantitative correlation research design. A sample of 34 students was randomly selected, and data was collected through a validated questionnaire with a Cronbach's alpha value of 0.894. Analysis was conducted using normality tests, linearity tests, and product-moment correlation tests with SPSS software, showing a significance value of 0.000, indicating a significant relationship. The Pearson correlation coefficient was 0.765, suggesting a strong relationship between peer social support and academic resilience. The study concludes that higher peer social support leads to increased academic resilience among students.